Nanofiltration membrane predictive models / Norhaslina Mohd Sidek and Nora’aini Ali - Mohd Sidek, Norhaslina; Ali, Nora’aini (2012)
Literature models for nanofiltration (NF) are usually based either on a mechanism-independent approach, such as irreversible thermodynamics (IT), or depending on transport mechanism (hydrodynamic approach). Most current IT models are based on the work of Spiegler and Kedem. For the mechanistic models; it is divided into two categories: those based on the Space Charge (SC) model and Teorell-Meyer–Sievers (TMS) model. These approaches have been used in order to determine the ion transport mechanisms during separation process which is commonly governed by both of steric and charge effects.